2019
DOI: 10.1021/acssynbio.9b00034
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Assembly of Complex Giant Unilamellar Vesicle-Based Synthetic Cells

Abstract: Here, we introduce a one-pot method for the bottom-up assembly of complex single- and multicompartment synthetic cells. Cellular components are enclosed within giant unilamellar vesicles (GUVs), produced at the milliliter scale directly from small unilamellar vesicles (SUVs) or proteoliposomes with only basic laboratory equipment within minutes. Toward this end, we layer an aqueous solution, containing SUVs and all biocomponents, on top of an oil–surfactant mix. Manual shaking induces the spontaneous formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
180
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(186 citation statements)
references
References 47 publications
(110 reference statements)
4
180
0
Order By: Relevance
“…Accordingly, manipulating the charge on the vesicles could lead to more stable multiple compartments. 12 Another strategy to create stable multiple compartments is achieved by including PEG 8000 in the buffer to the DOPC:DOPG mixture lipid lm (Video S4 †). However, the efficiency of encapsulating vesicles in GUVs is low compared to that of microuidic techniques.…”
Section: Multiple Compartments In Vesiclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, manipulating the charge on the vesicles could lead to more stable multiple compartments. 12 Another strategy to create stable multiple compartments is achieved by including PEG 8000 in the buffer to the DOPC:DOPG mixture lipid lm (Video S4 †). However, the efficiency of encapsulating vesicles in GUVs is low compared to that of microuidic techniques.…”
Section: Multiple Compartments In Vesiclesmentioning
confidence: 99%
“…Another hypothesis might be that some proportion (close to 5-10%) of the vesicles are multilamellar, as observed for other methods as well. 12 Also, we present the data for different individual GUVs measured at both pH 5 (n ¼ 8) and pH 7 (n ¼ 9) and corresponding I in /I out changing at different rates conrming varying protein reconstitution in different GUVs (Fig. S13 †).…”
Section: Functionality Of Liposomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesicles were usually utilized for fabricating artificial cell models and applied for understanding biological cells . It was reported that the compartmental vesicle was applied as the hypothetical precursor of cell at the origin of life . Correspondingly, preparation size‐controllable monodisperse vesosomes should be the first problem to be solved for fabricating artificial cells.…”
Section: Synthesizing Artificial Cells By Microfluidicsmentioning
confidence: 99%
“…[219][220][221] It was reported that the compartmental vesicle was applied as the hypothetical precursor of cell at the origin of life. [222][223][224] Correspondingly, preparation size-controllable monodisperse vesosomes should be the first problem to be solved for fabricating artificial cells. Microfluidic devicebased methods may help to achieve this goal by taking advantages of the ability to control vesicular structures.…”
Section: Synthesizing Vesicle-based Artificial Cells By Microfluidicsmentioning
confidence: 99%